Teknologisasi Pertunjukan Dalam Kontestasi Dramaturgi Tradisi dan Modern Bagi Ketahanan Nasional - Yudiaryani; Kuardhani, Hirwan; Pungkiawan, Pius Rino; A. Purba, Silvia; Haryono, A. Janu; Rahmah, Fitri (PANGGUNG, 2026)
Theatre develops through shifting relations among body, space, and technology. Digital mediation does not merely introduce new aesthetic instruments but reconfigures dramaturgical structures and modes of knowledge production. Dramaturgy, therefore, must be understood as an epistemic practice organizing interactions among body, media, and spectatorship rather than as textual composition alone. This article reads the technologization of theatre as a shift from representation toward performativity and interactivity. The encounter between traditional and contemporary practices reveals technology as a negotiated field: disruptive within certain value systems yet generative of new aesthetic and conceptual possibilities. Through dramaturgical analysis, three interrelated configurations are identified—mimetic, epicising, and interactive—through which technologization operates as an epistemic condition. Theatre thus appears not only as artistic production but as practice-as-research, where knowledge emerges through performative processes.